Focusing on content or strategies? Enactment of reading strategies in discussions about science texts. Issue 4 (2nd October 2022) - Walldén, Robert
ABSTRACT: This article concerns the relationship between general literacy skills and engagement with subject-specific content in classroom practice. The aim is to contribute knowledge about how enactment of reading strategies impacts classroom discussions about science texts. For 10 weeks, the researcher conducted observations and audio recordings of strategy-focused text discussions in Grade 4 physics and biology. The strategies employed were as follows: text knowledge, looking at text features and using prior knowledge. The analysis of the transcribed recordings and relevant parts of the textbook material was informed by Bernstein's sociology of education and a social semiotic view of disciplinary literacy practices. The result shows that reading strategies were foregrounded in discussions about texts in ways which created and upheld boundaries to related content, activities and texts. Notably, the teacher and the students discussed single pages of science textbook material without considering how meaning conveyed by images and writing relates to other pages by, for example, bringing technical knowledge closer to everyday experience or by condensing meanings in a technical way. The study shows the potential of adhering to the information flow between given and new on textbook spreads to understand shifts between concrete and technical meaning.